2019
DOI: 10.15802/stp2019/170273
|View full text |Cite
|
Sign up to set email alerts
|

Method for Predicting Parameters of the Aeroionic Mode in Open Terrain Ground Areas

Abstract: Purpose. The scientific work is devoted to the development of a new method for forecasting aeroionic mode in working areas at industrial sites, taking into account ionizing sources and surrounding obstacles. Methodology. To find the concentration of positive aeroions, dust and negative aeroions, we use 3D mass transfer equations that take into account the rate of recombination of ions having different polarity and the rate of recombination of ions with dust particles. The numerical solution is based on the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Changes in the concentration of ions are due to the operation of the fan and the corresponding electrifying of the body. Work [9] modeled the spread of ions from sources of ionization and deionization of air, in particular in the presence of several computerized workplaces. It is shown that the distribution of ions is influenced by the location of equipment, in particular dissecting surfaces.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the concentration of ions are due to the operation of the fan and the corresponding electrifying of the body. Work [9] modeled the spread of ions from sources of ionization and deionization of air, in particular in the presence of several computerized workplaces. It is shown that the distribution of ions is influenced by the location of equipment, in particular dissecting surfaces.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Data in Tables 8, 9 data indicate the positive impact of such devices on the ion composition of the air. Patterns regarding their distribution in space and time are easy to calculate based on the functions given in [9]. It should be noted that in printers and photocopiers in the paper feed nodes there are crown discharges that generate ions.…”
Section: Tablementioning
confidence: 99%